New Economy - Dehio, Jochen; Döhrn, Roland; Loeffelholz, Hans Dietrich von; Moos, Waike; Graskamp, Rainer; Löbbe, Klaus; Rothgang, Michael (Duncker & Humblot, 2024)
For many observers the beginning of a dynamic economic and stock market upswing in the U.S. in the mid 1990s marked the start of a new era, the times of the new economy. This phenomenon has been under intense discussion ever since - both in the political arena as well as among scientists. Thereby the somewhat glamorous term new economy reflects the conviction held by its proponents that the use of new technologies will lead to a never ending acceleration of technological progress and economic welfare.